Prevalence of Regional Wall Motion Abnormalities in Patients Coronary Artery Disease at Tangerang District Hospital - Hasni, Hasni; Nauli, Siti Elkana; Budiman, Muhamad Arif (Muhammadiyah Medical Journal, 2024)
Background: Coronary artery disease (CAD) is when the coronary blood vessels cannot supply blood to the heart due to a pile of atherosclerotic plaque in the coronary arteries, so blood flow to the myocardium is disrupted. This blood flow disturbance will cause myocardial contractile dysfunction and Regional Wall Motion Abnormalities (RWMA). Purposes: This study aims to determine the prevalence of Regional Wall Motion Abnormalities in CAD patients based on a single-center study at Tangerang District Hospital in January - May 2024. Methods: Our study used a descriptive approach in 130 CAD patients grouped based on gender, age, hypertension, and diabetes mellitus. In addition, the determination of RWMA severity cases in CAD was measured by only the Wall Motion Score Index (WMSI) and Wall Motion Score Index (WMSI) followed by the Bull's-eye plot parameters. Results: The prevalence of CAD patients with RWMA using the WMSI method was found to be 41 patients (32%) who were predominantly male (76%) and occurred at the mean of age 61,14 years, 27% hypertension, and 17% diabetes mellitus. Conclusion: WMSI parameters followed by the Bull's-eye plot could identify 14.6% more RWMA cases than only WMSI.